THE EFFECT OF TQM PRACTICES ON OPERATIONAL PERFORMANCE IN ENERGY SECTOR COMPANIES - Fahira, Shandrina; Sentosa, Wahyuningsih (Universitas Negeri Yogyakarta, 2023)
This study aims to determine whether there is an influence of TQM Practice on operational performance in energy companies in Indonesia. The sample selection method in this study is Purposive Sampling in employees who work in the field of energy, Data collection using surveys in the form of questionnairesusing SEM statistical analysis tools processed through AMOS 26 software. The results of hypothesis testing show that process management has a positive and significant effect on performance, while top management support, customer focus, employee empowerment and engagement, continuous improvement, education and training have no significant effect.